2015
DOI: 10.1519/jsc.0000000000000987
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Elastic Bands on Kinetic Characteristics During the Deadlift at Moderate and Heavy Loads

Abstract: Loading a barbell with variable resistance positively alters kinetic characteristics during the back squat and bench press but has never been studied during the deadlift. The purpose of this project was to examine the acute effects of combining elastic bands and free weights during the deadlift at moderate and heavy loads. Twelve trained men (age: 24.08 ± 2.35 years, height: 175.94 ± 5.38 cm, mass: 85.58 ± 12.49 kg, deadlift 1 repetition maximum (RM): 188.64 ± 16.13 kg) completed 2 variable resistance (B1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 29 publications
(61 reference statements)
5
37
1
Order By: Relevance
“…These results highlight that the modality of accommodating resistance may influence the effects of VRT. This was supported in two further studies on kinetics, which showed that, performing the deadlift decreased bar power and velocity with chains (19) but increased bar power and velocity with bands (11).…”
Section: Introductionmentioning
confidence: 67%
“…These results highlight that the modality of accommodating resistance may influence the effects of VRT. This was supported in two further studies on kinetics, which showed that, performing the deadlift decreased bar power and velocity with chains (19) but increased bar power and velocity with bands (11).…”
Section: Introductionmentioning
confidence: 67%
“…Namely, in training and the competition itself, the athletes overcome certain external load which has two main componentsgravitational and inertialwhere their neglecting lessens the information power of the tests. Previous studies have examined the impact of the different types of loads to the effects of training (Anderson, Sforzo, & Sigg, 2008;Galpin et al, 2015;Saeterbakken, Andersen, Kolnes, & Fimland, 2014;Stevenson, Warpeha, Dietz, Giveans, & Erdman, 2010;Wallace, Winchester, & McGuigan, 2006). The findings of the studies mentioned have confirmed that application of different types of loads (usage of weights, rubber bands and their combination) lead to different effects of training.…”
Section: Introductionmentioning
confidence: 73%
“…However, power was unaffected in their study, which may have been due to the relatively heavy loads used. Galpin (Galpin et al, 2015) also examined the effects of different loads using variable resistance. Their study used banded deadlifts at 60% and 85% 1RM using different resistances (B1=15% resistance, B2 = 35% resistance.)…”
Section: Discussionmentioning
confidence: 99%